Electrodeposition and characterisation of Cu–MWCNTs nanocomposite coatings. (4th May 2017) - Ramalingam, S.; Balakrishnan, K.; Shanmugasamy, S.; Subramania, A.
Abstract : The Cu–Multi-walled carbon nanotubes (MWCNTs) nanocomposite coatings were prepared by the electrodeposition process using MWCNTs in an acid copper plating bath under optimised bath composition and process conditions. The Cu–MWCNTs nanocomposite thin film was characterised for structural, mechanical and anti-corrosion properties. The X-ray diffraction confirmed the crystallite structures and texture of pure copper and Cu–MWCNTs nanocomposite coatings. The field emission scanning electron microscopy showed that the MWCNTs were uniformly distributed in the copper matrix as fine crystallites. The Vickers microhardness test results showed that the microhardness of Cu–MWCNTs nanocomposite coating was much higher than that of the pure copper coating. The electrochemical AC-impedance and Tafel polarisation studies confirmed that the Cu–MWCNTs nanocomposite coating was found to have higher corrosion resistance than the pure copper coating in 3.5% NaCl (w/v) solution.